Kurikulum Pendidikan Islam yang Berorientasi pada Keterampilan Abad 21 (Pemikiran Ibnu Maskawaih) - Nurhalimah Nurhalimah (Departement of Mathematics Education, 2024)
This study aims to explore and analyze the integration of Ibn Maskawih's thoughts in the development of an Islamic education curriculum oriented to 21st century skills. In the context of globalization and rapid technological development, education is expected to not only focus on mastering knowledge, but also on the formation of students' character and social skills. A qualitative approach was used in this study to collect data through in-depth interviews, observations, and documentation studies involving educators, students, and education experts. The results of the study indicate that Ibn Maskawih's thoughts, which emphasize holistic education, are very relevant to be applied in the current Islamic education curriculum. He emphasized the importance of balanced moral, spiritual, and intellectual development, which can create individuals who are not only academically intelligent but also have good character. By integrating ethical and moral values ​​in learning, the Islamic education curriculum can function as a tool to form students who are responsible and able to face complex social challenges. This study identifies the important role of technology in supporting interactive and collaborative learning processes. The use of digital platforms, learning applications, and social media not only increases students' access to information but also encourages their active involvement in the learning process. Thus, technology can be an effective tool in developing 21st century skills, such as critical thinking, creativity, collaboration, and communication. This study also emphasizes the importance of balance between science and religious teachings, where both aspects complement each other in forming a whole individual. With a holistic and integrative approach, Islamic education can produce graduates who are not only competent in academics, but also have strong ethics and are able to contribute positively to society.